2007
DOI: 10.3892/or.17.5.1171
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of RIN1 gene expression in colorectal cancer

Abstract: The RIN1 gene, located on chromosome 11q13.2, is a molecule consisting of a coding region of 2352 bp, has a domain on the 3' side that binds to H-Ras protein, and is presumed to be an important molecule in an intracellular signaling pathway. Since the RIN1 molecule belonging to the effector molecules of H-Ras has not been reported in colorectal or other digestive tract cancers to date, we investigated how the RIN1 gene was involved in colorectal cancer. Fifty-two (51.5%) of 101 colorectal cancer specimens stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…A similar prognostic correlation was reported in non-small-cell lung cancer and in gastric tumors (Wang et al 2012). In colorectal tumors, Rin1 expression correlated not only with poor prognosis but also with venous invasion (Senda et al 2007). Congruent with growth-factor-driven invasiveness and metastasis, studies performed on lung cancer cell lines suggested that Rin1 regulates cell proliferation through EGFR (Tomshine et al 2009).…”
Section: Endocytosis and Cancersupporting
confidence: 74%
“…A similar prognostic correlation was reported in non-small-cell lung cancer and in gastric tumors (Wang et al 2012). In colorectal tumors, Rin1 expression correlated not only with poor prognosis but also with venous invasion (Senda et al 2007). Congruent with growth-factor-driven invasiveness and metastasis, studies performed on lung cancer cell lines suggested that Rin1 regulates cell proliferation through EGFR (Tomshine et al 2009).…”
Section: Endocytosis and Cancersupporting
confidence: 74%
“…From this present study, RIN1 was localized at the cytoplasm in the head and neck tumor tissues (Figs 2 and 3). This is consistent with a study by Senda et al (2007). From their study, RIN1 was found in the cytoplasm of colorectal cancer.…”
Section: Discussionsupporting
confidence: 93%
“…This is similar to a study by Milstein et al (2007), who observed that the level of RIN1 was silenced in breast tumor tissues. In contrast, RIN1 expression levels were reported to be elevated in various tumors, including gastric adenocarcinoma [ 19 ], colorectal cancer [ 17 ], non-small cell lung cancer [ 12 ], and bladder urothelial carcinoma [ 20 ]. RIN1 transcript levels from head and neck tumors and normal head and neck tissues were also determined with real-time polymerase chain reaction (RT-PCR) ( Fig 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Ras occupation of the Rin1 Ras association domain positively impacts the Rab5 GEF activity of Rin1, which promotes EGFR internalization and attenuation in fibroblasts (23). However, Rin1 expression is up-regulated in several types of cancers, including squamous cell carcinoma (24), colorectal cancer (25), and cervical cancer (26), through duplications or rearrangements of the RIN1 locus. These studies suggest that Rin1 may also play a role in enhancing cell proliferation.…”
mentioning
confidence: 99%